Sharing of attacks information across clouds for improving security:a conceptual framework - Waqas, Ahmad; Muhammed Yusof, Zulkefli; Shah, Asadullah; Mahmood , Nadeem (2014)
Cloud computing has recently emerged as a new paradgim for hosting and delivering services over the Internet. It is evolving as a key computing platform for sharing resources that include infrastructure, software, applications, and business processes. The cloud environment is required to have efficient security techniques as it contains precious assets such as data, users, technologies, resources and business transactions. Most of the proposed architectures for cloud computing implementations are for individual clouds which do not allow the sharing of attacks information with other clouds and hence the other clouds are not ale to safe themselves from the same attacks. The aim of this research is to propose a conceptual framework for connected or federated clouds that can share information regarding attacks and attackers for securing themselves.